The Residual-Free-Bubble Finite Element Method on Anisotropic Partitions. - Cangiani, A; Süli, E (2007)
The subject of this work is the analysis and implementation of stabilized finite element methods on anisotropic meshes. We develop the anisotropic a priori error analysis of the residual-free-bubble (RFB) method applied to elliptic convection-dominated convection-diffusion problems in two dimensions, with finite element spaces of type Qk., k ≥ 1. In the case of P1 finite elements, relying on the equivalence of the RFB method to classical stabilized finite element methods, we propose a new rule, justified through the analysis of the RFB method, for selecting the stabilization parameter in classical stabilized methods on two-dimensional anisotropic triangulations. © 2007 Society for Industrial and Applied Mathematics.